Effect of Bi3+ ion on upconversion-based induced optical heating and temperature sensing characteristics in the Er3+/Yb3+ co-doped La2O3 nano-phosphor - Yadav R.S.; Kumar D.; Singh A.K.; Rai E.; Rai S.B. (My University, 2025)
The upconversion-based optical heating and temperature sensing characteristics are investigated in the Er3+/Yb3+/Bi3+ tri-doped La2O3 nano-phosphor synthesized through a solution combustion method. The structural measurements reveal an increase in lattice parameters and particles size of the phosphor on increasing the concentrations of Bi3+ ions. The energy dispersive spectroscopic (EDS) measurements confirm the presence of La, Er, Yb, Bi and O elements in the tri-doped phosphor. The absorption spectra show the large number of bands due to Er3+, Yb3+ and Bi3+ ions. The Er3+/Yb3+ co-doped phosphor gives strong green emission bands at 523 and 548 nm upon 976 nm excitation due to 2H11/2 → 4I15/2 and 4S3/2 → 4I15/2 transitions of Er3+ ion, respectively. The emission intensity of these bands is enhanced upto 15 times in the presence of Bi3+ ions. The emission intensities of the 523 and 548 nm bands vary non-linearly with the pump power. The fluorescence intensity ratio (FIR) of the thermally coupled 523 and 548 nm emission bands shows efficient optical heating in the tri-doped phosphor. The FIR of the 523 and 548 nm emission bands further varies with the increase in temperature of the phosphor. The relative temperature sensing sensitivity has been calculated to be 71 × 10−4 K−1 at 450 K for the tri-doped phosphor. Thus, the Er3+/Yb3+/Bi3+ tri-doped La2O3 nano-phosphor may provide a platform to use it in the photonic devices, as an optical heater and temperature sensor. © The Royal Society of Chemistry.